STRATEGY DEVELOPMENT FARMING CHILLI RED IN PEMATANG BANDAR DISTRICT REGENCY SIMALUNGUN - Amelia Junita; Ade Firmansyah Tanjung; Sakral Hasby; Setia Budi; Nopri Yanto (Jurnal Mahasiswa Agribisnis, 2026)
This study was conducted in Pematang Bandar Subdistrict, Simalungun Regency, with the aim of analyzing strategies for developing red chili farming in embankment port Subdistrict t, Simalungun Regency, through a SWOT and QSPM analysis approach. Data was obtained from 21 red chilli farmer respondents using interviews, observations, and questionnaires. The SWOT analysis results showed that the identification of internal and external factors in red chilli farming in Pematang Bandar Subdistrict consisted of 4 internal strengths and 4 internal weaknesses, while external factors resulting in 3 opportunities and 3 threats. Based on the QSPM calculation results, the priority The strategy chosen is to improve the quality and quantity of production through the application of better cultivation technology, the use of superior seeds, and integrated pest control, with a total attractiveness score (TAS) of 6.68.